Analisis Pengaruh Karakteristik Merk, Karakteristik Perusahaan, Dan Karakteristik Konsumen Merk Pada Loyalitas Penggunaan Telepon Seluler Berbasis CDMA - , Rismania Veradiza, Dr. Ike Janita Dewi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Brand is an important element in the consumer market because brand is the interface between consumers and the company, and consumers may develop loyalty to the brand. This study test that trust in brand is very important and is a key element to develop brand loyalty. Factors hypothesized to influence trust in a brand include a number of brand characteristics, company characteristics, and consumer-brand characteristics. This research also aims to identify the differences trust in brand and brand loyalty in customers based on segmentation of age, socioeconomic status, marital status, education level, and gender. Respondents of this study are the customer of Flexi Trendy, namely brand of CDMA mobile phone service by PT. Telekomunikasi Indonesia, Tbk. The survey is conducted to the customers of Flexi Trendy who lives in Jabodetabek area. Sample was obtained using judgment sampling technique to Prepaid Customers of Flexi who lives in Jabodetabek area. Data was collected during October 2010. These research results indicate that brandâs characteristics, brand-consumerâs characteristics, and company characteristics together affect trust in brand with a value of adjusted R 2 0.802. The consumer-brand characteristics have greater impact on trust in brand with the standardized coefficient betaâs value 0.505. Other findings from this study is that trust in brand positively affects brand loyalty with value of the standardized coefficient beta 0.881 and adjusted R 2 0.774. Trust in brand has different levels based in the segmentation of gender, marital status, education level, and socioeconomic status. Meanwhile, different levels of brand loyalty also appear among customers based on gender, marital status, and socioeconomic status with significance value below 0.05. Therefore, PT. Telekomunikasi Indonesia, Tbk, especially Telkom Flexi Division as a product owner must consider the characteristics of consumerbrand to develop trust in brand among the target market.